The role of inflammation and apoptosis in cyclosporine A – induced gingival overgrowth - Kristina Mitic; Mirjana Popovska; Maja Pandilova; Rubens Jovanovic; Goce Spasovski; Vladimir Nikolov (Biomolecules & Biomedicine, 2013)
Cyclosporin A(CsA) - induced gingival overgrowth(GO) is a current problem of tissue-specific mechanism which is still incompletely explained. The apoptotic process has been of particular interest like a new concept in the etiology of this unwanted effect.